Size distribution and formation processes of aerosol water-soluble organic carbon during winter and summer in urban Beijing. (1st January 2021) - Ni, Xue; Pan, Yuepeng; Shao, Peng; Tian, Shili; Zong, Zheng; Gu, Mengna; Liu, Bowen; Liu, Jin; Cao, Jing; Sun, Qian; Wang, Yuesi; Jiang, Changsheng
Abstract: Size-resolved aerosol organic carbon (OC) and water-soluble OC (WSOC) was determined weekly in urban Beijing between 2013 and 2018. The results showed that in winter, the concentrations of WSOC and OC in fine (<2.1 μm) and coarse (>2.1 μm) mode were highest in 2013. During the following years, the concentrations of WSOC and OC were lower but an increasing trend was found from 2014 to 2016, which might be due to the increasing precursor concentrations. From summer 2013 to 2018, the concentrations of OC and WSOC in both fine and coarse mode decreased, which might be affected by decreasing emission intensity and photochemical oxidation. To characterize the seasonality of WSOC, two intensive field observations were further performed in winter 2013 and summer 2018. In winter of 2013, WSOC was mainly enriched in PM1 (<1 μm) on clean days and lightly polluted days. In addition, the fine mode maximum shifted from 0.43-0.65 μm to 1.1–2.1 μm with the haze development due to the hygroscopic growth of particles. In summer of 2018, the WSOC was mainly concentrated in PM1, but in a few samples, the maximum size appeared in coarse mode. This difference might due to the different relative humidity and air mass sources. While the formation process of WSOC in winter was affected by photochemical oxidation below 2.1 μm, in 1.1–2.1 μm, it tended to change from photochemical oxidation to aqueous-phase oxidation. For the coarse mode WSOC formation in winter, however, it was mainly affected by heterogeneous processes. The findings advanced our understanding of the annual trends, size distribution and formation processes of WSOC, with significant implications for air pollution control in Beijing and surrounding regions. Graphical abstract: Image 1 Highlights: Carbonaceous species in both fine and coarse modes decreased from 2013 to 2018. The size distribution of WSOC shifted from fine to coarse during haze episodes. In summer, coarse mode WSOC was mainly condensed on sea salt. In winter, WSOC formation was affected by secondary processes.